Role of Product Placement, E-WOM, and Brand Awareness on Purchase Decision - Arif, Moh. Erfan; Rabba, Alya Zikrina (Jurnal Riset Manajemen dan Bisnis, 2024)
Abstract. This study aims to determine the effect of product placement on Korean Drama and electronic word of mouth on purchase decision with brand awareness as mediation on Kopiko Candy. This type of research is explanatory with a quantitative approach to determine the relationship between variables. Data from 380 respondents were collected through surveys with non-probability sampling techniques. The characteristics of respondents are over 17 years old, have watched Korean dramas that have Kopiko advertisements, have bought Kopiko products and have read Kopiko reviews via the internet. The analysis method uses the SEM-PLS approach through inner and outer model testing. Hypothesis testing was tested using SmartPLS by paying attention to the results of the t test on bootstrapping. The test results show that product placement has no effect on purchase decision. However, electronic word of mouth and brand awareness have a positive effect on purchase decision. In addition, product placement and electronic word of mouth have a positive effect on brand awareness and brand awareness can mediate the effect of product placement and electronic word of mouth on purchase decision. Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh product placement pada drama korea dan electronic word of mouth terhadap purchase decision dengan brand awareness sebagai mediasi pada produk Kopiko. Jenis penelitian ini adalah penelitian ini adalah eksplanatori dengan pendekatan kuantitatif yang mencari hubungan antar variabel serta menjelaskan sebab akibat dari fenomena sosial yang diteliti. Pada penelitian ini mengambil data dari 380 responden dengan teknik non-probability sampling. Karateristik responden yang diteliti yaitu berumur diatas 17 tahun, pernah menonton drama Korea yang didalamnya terdapat iklan Kopiko, pernah membeli produk kopiko dan pernah membaca review Kopiko melalui internet. hasil menunjukkan bahwa variabel product placement tidak memiliki pengaruh sedangkan variabel electronic word of mouth berpengaruh terhdadap purchase decision. Variabel product placement dan electronic word of mouth memiliki pengaruh positif terhadap brand awareness. Demikian juga variabel brand awareness memiliki pengaruh positif  terhadap variabel purchase decision. Hasil juga menunjukan bahwa variabel brand awareness dapat memediasi pengaruh variabel product placement dan electronic word of mouth secara tidak langsung terhadap purchase decision.